Longitudinal Relationships of Fitness, Physical Activity, and Weight Status With Academic Achievement in Adolescents. (12th September 2016) - Suchert, Vivien; Hanewinkel, Reiner; Isensee, Barbara
ABSTRACT: BACKGROUND: To examine associations of cardiorespiratory fitness, physical activity (PA) and weight status with academic achievement 1 year later. In addition, the mediating role of psychological variables was tested. METHODS: Longitudinal analyses included 1011 German students (M = 14.1 years, SD = 0.6 years). Cardiorespiratory fitness was determined with the 20 m shuttle run test. Compliance with PA guidelines was assessed through questionnaire. Weight status was based on body mass index percentiles. As proxy of academic achievement students' self‐reported grades in Mathematics and German in their midterm report were averaged. Mediation analyses were conducted at follow‐up testing general self‐efficacy, depressed affect, and attention/hyperactivity problems. RESULTS: High levels of cardiorespiratory fitness predicted higher educational attainment (p = .007), while we found no longitudinal association for PA and weight status (p > .253). However, students being insufficiently physically active at baseline but meet PA guidelines at follow‐up showed a significant improvement in educational attainment. The cross‐sectional association between PA and academic achievement was mediated by students' general self‐efficacy. CONCLUSION: High fitness in adolescence is associated with higher subsequent academic achievement. The promotion of PA might benefit school performance because of enhanced fitness levels in the long‐term and positive influences of PA in the shortterm. The association between weight status and educational attainment remains controversial.